2011
DOI: 10.7705/biomedica.v31i4.395
|View full text |Cite
|
Sign up to set email alerts
|

Evaluación de la seroconversión como respuesta a la vacunación antirrábica en perros en el departamento del Valle del Cauca, Colombia, 2009

Abstract: Resultados. El 9,1 % de los perros de la muestra fueron seronegativos y el 25,1 % no evidenciaron respuesta inmunitaria humoral adecuada a la vacunación. La concentración de anticuerpos disminuyó gradualmente desde la aplicación de la vacuna, y estuvo asociada a edad y calidad de las vacunas, aunque no estuvo asociada a sexo ni a raza. Conclusiones. Con el fin de aumentar los porcentajes de perros seropositivos y con respuesta inmunitaria humoral adecuada, se hacen las siguientes recomendaciones: 1) utilizar v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
4
1
2

Year Published

2014
2014
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 20 publications
0
4
1
2
Order By: Relevance
“…Notably, although 71.53% of the vaccinated dogs did not develop neutralizing humoral immunity, only 44.83% of the cats vaccinated in the mass vaccination campaigns of the second half of 2015 did not develop neutralizing antibodies. These results in dogs are far from the results reported by Paez et al (Páez et al 2011), who demonstrated that 74.9% of dogs had an adequate humoral immune response, that is, at levels equal to or higher than 0.5 IU/ml. In the case of cats, the present study is the first one in Colombia that shows the results of the anti-rabies immune response in cats in the country.…”
Section: Discussioncontrasting
confidence: 91%
See 3 more Smart Citations
“…Notably, although 71.53% of the vaccinated dogs did not develop neutralizing humoral immunity, only 44.83% of the cats vaccinated in the mass vaccination campaigns of the second half of 2015 did not develop neutralizing antibodies. These results in dogs are far from the results reported by Paez et al (Páez et al 2011), who demonstrated that 74.9% of dogs had an adequate humoral immune response, that is, at levels equal to or higher than 0.5 IU/ml. In the case of cats, the present study is the first one in Colombia that shows the results of the anti-rabies immune response in cats in the country.…”
Section: Discussioncontrasting
confidence: 91%
“…However, although the vaccination card was reviewed (data not shown), the information provided in these cards by the personnel responsible for vaccinations was inconsistent and incomplete and did not allow the evaluation of vaccine-related variables that could explain the low rate of seroconversion. This information could be confirmed in the study by (Páez et al 2011), demonstrating that there may be vaccines and/or batches that do not allow the production of effective antibody titers (Páez et al 2011). The differences found in the level of seroconversion among animal shelters (Fig.4) allow us to assume that there are anthropogenic variables that influence the immune response of vaccinated animals.…”
Section: Discussionmentioning
confidence: 80%
See 2 more Smart Citations
“…The low concentration of antibody titers in dogs vaccinated against rabies has been previously reported [ 16 - 19 ]. Similarly, the immune response of dogs vaccinated only one time has already been evaluated and the results showed a rapid drop of antibody titers, which suggests that several animals are unprotected among vaccination campaigns [ 10 , 20 ].…”
Section: Resultsmentioning
confidence: 92%